2019
DOI: 10.3390/s19235130
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy with a Fiber-Coupled Quantum Cascade Laser for Attenuated Total Reflection Measurements Towards Biomedical Applications

Abstract: The development of rapid and accurate biomedical laser spectroscopy systems in the mid-infrared has been enabled by the commercial availability of external-cavity quantum cascade lasers (EC-QCLs). EC-QCLs are a preferable alternative to benchtop instruments such as Fourier transform infrared spectrometers for sensor development as they are small and have high spectral power density. They also allow for the investigation of multiple analytes due to their broad tuneability and through the use of multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…One option is to use a smaller single-reflection IRE with signal-enhancement, which has given good preliminary results in the same setup as used here [33]. As discussed in our earlier study [26], a commercialised QCL-based sensor will also likely require the use of a few fixed-wavelength lasers for cost and size reduction instead of a tuneable laser. Some previous QCL studies on glucose measurements have explored concentration predictions with only a few wavenumbers [34,35], which has demonstrated that this is a possible avenue for sensor development.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One option is to use a smaller single-reflection IRE with signal-enhancement, which has given good preliminary results in the same setup as used here [33]. As discussed in our earlier study [26], a commercialised QCL-based sensor will also likely require the use of a few fixed-wavelength lasers for cost and size reduction instead of a tuneable laser. Some previous QCL studies on glucose measurements have explored concentration predictions with only a few wavenumbers [34,35], which has demonstrated that this is a possible avenue for sensor development.…”
Section: Discussionmentioning
confidence: 97%
“…This prism had a surface area of 24 mm x 2.4 mm, and a height of 1.2 mm. The thickness of this prism was half of that used in our previous ATR experiments [26], and it had 11 reflections on the top surface. Hollow-core optical fibres with an inner diameter of 1 mm were used for in-and out-coupling of light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although chalcogenide glass optical fiber and polycrystalline optical fiber are commercially available as types of mid-infrared optical fiber, the latter is advantageous because it does not contain toxic material prohibited from being used in biomedical applications. Various proposals for spectroscopic systems using a QCL and AgCl/AgBr polycrystalline optical fiber have been made [ 6 , 7 ]. Moreover, because of its simpler structure, a hollow optical fiber is advantageous in terms of cost and durability as an optical transmission medium for mid-infrared spectroscopy systems.…”
Section: Introductionmentioning
confidence: 99%
“…The QCL-based systems have already been applied to various biomedical applications [ 13 ] including the detection of NO gas [ 14 ], ammonia detection [ 15 ] in breath, blood glucose concentration measurement [ 7 , 16 , 17 , 18 ], and drug detection in saliva [ 19 ]. For these application systems, an external cavity-type QCL (EC-QCL) capable of wavelength sweeping is typically used.…”
Section: Introductionmentioning
confidence: 99%